2013
DOI: 10.1158/1078-0432.ccr-13-1414
|View full text |Cite
|
Sign up to set email alerts
|

ECOG Phase II Trial of Graded-Dose Peginterferon α-2b in Patients with Metastatic Melanoma Overexpressing Basic Fibroblast Growth Factor (E2602)

Abstract: Purpose We investigated use of graded-dose peginterferon α-2b (Peg-IFN) in patients with stage IV melanoma overexpressing basic fibroblast growth factor (FGF-2). The primary objective was suppression of plasma FGF-2 to within normal range (≤7.5 pg/mL). Experimental Design Plasma FGF-2 was measured at baseline (Step 1), and patients with concentrations ≥15 pg/mL were eligible for study treatment (Step 2). Peg-IFN was given weekly at starting dose of 0.5 μg/kg/wk with increment every 3 weeks based on serial FG… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…AGM-1470, miRNA 646, and interferon alpha downregulate FGF2 expression in cancer cells (Table 5, Figure 4). A phase II clinical study was conducted to evaluate the efficacy of pegintron (peginterferon alpha-2b) in patients with stage IV metastatic melanoma overexpressing FGF2 (Table 6) [87]. The results showed that peginterferon alpha-2b suppressed FGF2 levels in 97% of patients with metastatic melanoma to reference range with a median progression free survival (PFS) and overall survival (OS) of 2.0 and 9.7 months, respectively (Table 6) [87].…”
Section: Targeting the Fgf2/fgfr Pathway In Cancermentioning
confidence: 99%
“…AGM-1470, miRNA 646, and interferon alpha downregulate FGF2 expression in cancer cells (Table 5, Figure 4). A phase II clinical study was conducted to evaluate the efficacy of pegintron (peginterferon alpha-2b) in patients with stage IV metastatic melanoma overexpressing FGF2 (Table 6) [87]. The results showed that peginterferon alpha-2b suppressed FGF2 levels in 97% of patients with metastatic melanoma to reference range with a median progression free survival (PFS) and overall survival (OS) of 2.0 and 9.7 months, respectively (Table 6) [87].…”
Section: Targeting the Fgf2/fgfr Pathway In Cancermentioning
confidence: 99%
“…A375 cells and U87 cells were shown to express FGF-2 at high levels ( 19 21 ). Additionally, FGF-2 strongly stimulates the proliferation and migration of tumor cells ( 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…3b). Another clue is that low-dose IFN-α inhibits melanoma cell proliferation by interference with the autocrine growth circuit of FGF-2, a fibroblast growth factor belonging to the same family [29], an effect recently exploited to suppress FGF-2 in patients with metastatic melanoma [30]. Fig.…”
Section: Discussionmentioning
confidence: 99%